2014
DOI: 10.1016/j.ygyno.2014.07.094
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2A(p16) and HRAS are frequently mutated in vulvar squamous cell carcinoma

Abstract: Somatic mutations were detected in 62% of VSCCs. As expected, HPV infection and TP53-mutations play a key role in the development of VSCC, but CDKN2A(p16), HRAS, and PIK3CA-mutations were also frequently seen in HPV-negative patients. Patients with somatic mutations, especially HRAS-mutations, have a significantly worse prognosis than patients lacking these changes, which could be of importance for the development of targeted therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 32 publications
8
47
2
Order By: Relevance
“…p53 IHC was positive in only 5% of the unquestionably HPV‐associated tumors and in 66.7% of the unquestionably HPV‐independent tumors. These results are in keeping with previous reports showing that p53 abnormalities are infrequent in HPV‐associated tumors and present in about two‐thirds of HPV‐independent tumors . Interestingly, the percentage of p53 positivity in HPV DNA−/p16+ tumors was comparable to the unquestionably HPV‐associated neoplasms whereas HPV DNA+/p16− tumors were more similar to the indisputably HPV‐independent carcinomas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…p53 IHC was positive in only 5% of the unquestionably HPV‐associated tumors and in 66.7% of the unquestionably HPV‐independent tumors. These results are in keeping with previous reports showing that p53 abnormalities are infrequent in HPV‐associated tumors and present in about two‐thirds of HPV‐independent tumors . Interestingly, the percentage of p53 positivity in HPV DNA−/p16+ tumors was comparable to the unquestionably HPV‐associated neoplasms whereas HPV DNA+/p16− tumors were more similar to the indisputably HPV‐independent carcinomas.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in keeping with previous reports showing that p53 abnormalities are infrequent in HPV-associated tumors and present in about two-thirds of HPV-independent tumors. 14,49 Interestingly, the percentage of p53 positivity in HPV DNA2/ p161 tumors was comparable to the unquestionably HPVassociated neoplasms whereas HPV DNA1/p162 tumors were more similar to the indisputably HPV-independent carcinomas. These results add further evidence indicating that DNA2/ p161 tumors probably represent false-negative results of HPV DNA detection, whereas many of the HPV DNA1/p162 tumors are false-positive HPV DNA cases.…”
Section: Discussionmentioning
confidence: 92%
“…In total, 30% cervical cancers harbour PIK3CA mutations associated with poor outcomes following chemoradiotherapy (McIntyre et al , 2013; de la Rochefordiere et al , 2015), but similar findings are also reported in vulval (Trietsch et al , 2014) and penile cancers (McDaniel et al , 2015). Similarly the inverse relationship between HPV involvement and TP53 mutations is documented in HNSCC (Westra et al , 2008) and vulval cancer (Trietsch et al , 2014). …”
Section: Molecular Mechanisms For Differential Sensitivity To Crt In supporting
confidence: 64%
“…Previous work already identified somatic mutations in HRAS in HPV À VCs and showed an association with a worse prognosis (6). HRAS is an oncogene involved in the RTK/RAS/PI(3)K pathway, and somatic mutations lead to cell proliferation (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…5). Few studies have investigated genetic alterations in VCs and its precursor lesions beyond HPV status (6)(7)(8)(9)(10)(11). These studies have analyzed a limited selection of genes using Sanger sequencing or small panel hotspot approaches (8,10,11).…”
Section: Introductionmentioning
confidence: 99%